The Implementation of Extensive Green Roof Technology in High Rise Residential Building - Yui Tien, Tan; Yahya, Mohd Yamani (Research in Management of Technology and Business, 2020)
Extensive green roof designs have been widely implemented in developed countries, but not in Malaysia. Several factors contributed to the lack of implementation of the green roof in Malaysia, such as the lack of awareness among stakeholders of green roof technology, technical factors, economic factors, lack of skilled knowledge creation and limited local expertise and unexperienced green roof practitioners. The objectives of the research were to study the level of awareness among the stakeholders, to identify challenges and to identify the method encourage the implementation of extensive green roof in the high rise residential building. In this study, quantitative approach was used through the distribution of questionnaires to 45 stakeholders that have experience with extensive green roof in a high-rise residential building in Kuala Lumpur. Subsequently 40 respondents answered and returned the questionnaires and were analyzed using Statistical Package for Social Sciences (SPSS) software. In addition, the findings showed that the respondents had moderate levels of awareness; the most important challenges were knowledge of green roof systems; it is important to provide the right information for a large green roof; and the most successful approach was collaboration between the government and academics to conduct research. In conclusion, this research will help to increase the level of awareness among stakeholders in the implementation of a large green roof in high-rise residential buildings, the barrier of a large green roof can be tackled and the extensive green roof widely adopted in the construction sector can be promoted.